2013
DOI: 10.1186/2050-3385-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of attachment methods for pop-up satellite archival transmitters in European eel

Abstract: Background: Four methods for attaching pop-up satellite transmitters to European eel were tested in the laboratory by recording long-term tag retention, growth and survival; short-term behavioral responses; and physical damage from attachments. Results: All eels survived until they lost their tag, or until end of the six-month study. Specific growth rate did not differ between tagged fish and controls. Tag retention varied from 0% to 100% among attachment methods. A tagging method that uses the strength of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…PSAT tagging of longfin eel (Anguilla dieffenbachii) revealed a high rate of tag loss, with only three of 10 tags providing data [54]. Results from 275 silver European eel (A. anguilla) released on European coasts equipped with PSATs to study the ocean spawning migration indicated a large premature tag release [19]. This was partly related to mechanical tag loss, but also to a high predation rate (>20 % confirmed predation of eels with PSATs).…”
Section: Cebidichthys Violaceusmentioning
confidence: 99%
See 4 more Smart Citations
“…PSAT tagging of longfin eel (Anguilla dieffenbachii) revealed a high rate of tag loss, with only three of 10 tags providing data [54]. Results from 275 silver European eel (A. anguilla) released on European coasts equipped with PSATs to study the ocean spawning migration indicated a large premature tag release [19]. This was partly related to mechanical tag loss, but also to a high predation rate (>20 % confirmed predation of eels with PSATs).…”
Section: Cebidichthys Violaceusmentioning
confidence: 99%
“…Thus definitive records of external electronic tag retention, gained from recapture or direct observation, are most easily recorded in shallow, accessible environments, notably freshwater and clear inshore, marine environments. The recent, rapid development and application of pop-up tags has encouraged greater attention to effective attachment methods due to the high proportion of premature (before the pre-set time) releases when the attachment fails [7,19]. However, problems with retention of radio, acoustic, and data storage tags may be just as evident across many species in freshwater habitats.…”
Section: Tag Retentionmentioning
confidence: 99%
See 3 more Smart Citations